Biomechanical Research of Three Parallel Cannulated Compression Screws in Oblique Triangle Configuration for Fixation of Femoral Neck Unstable Fractures - Ru‐Yi Zhang; Wu‐Peng Zhang; Guang‐Min Yang; Dao‐Feng Wang; Peng Su; Yi Zhang; Shao‐Bo Nie; Jia Li; Zhe Zhao; Jian‐Tao Li; Li‐Cheng Zhang; Pei‐Fu Tang (Orthopaedic Surgery, 2024)
Objective Surgical treatment with internal fixation, specifically percutaneous fixation with three cannulated compression screws (CCSs), is the preferred choice for young and middle‐aged patients. The mechanical advantage of the optimal spatial configuration with three screws provides maximum dispersion and cortical support. We suspect that the spatial proportion of the oblique triangle configuration (OTC) in the cross‐section of the femoral neck isthmus (FNI) may significantly improve shear and fatigue resistance of the fixed structure, thereby stabilizing the internal fixation system in femoral neck fracture (FNF). This study aims to explore the mechanical features of OTC and provide a mechanical basis for its clinical application. Methods Twenty Sawbone femurs were prepared as Pauwels type III FNF models and divided equally into two fixation groups: OTC and inverted equilateral triangle configuration (IETC). Three 7.3 mm diameter cannulated compression screws (CCSs) were used for fixation. The specimens of FNF after screw internal fixation were subjected to static loading and cyclic loading tests, respectively, with five specimens for each test. Axial stiffness, 5 mm failure load, ultimate load, shear displacement, and frontal rotational angle of two fragments were evaluated. In the cyclic loading test, the load sizes were 700 N, 1400 N, and 2100 N, respectively, and the fracture end displacement was recorded. Results were presented as means ± SD. Data with normal distributions were compared by the Student's t test. Results In the static loading test, the axial stiffness, ultimate load, shear displacement, and frontal rotational angle of two fragments were (738.64 vs. 620.74) N/mm, (2957.61 vs. 2643.06) N, (4.67 vs. 5.39) mm, and (4.01 vs. 5.52)° (p < 0.05), respectively. Comparison between the femoral head displacement after 10,000 cycles of 700N cyclic loading and total displacement after 20,000 cycles of 700–1400N cyclic loading showed the OTC group was less than the IETC group (p < 0.05). A comparison of femoral head displacement after 10,000 cycles of 1400N and 2100N cycles and total displacement after 30,000 cycles of 700–2100N cycles showed the OTC group was less than another group, but the difference was not significant (p > 0.05). Conclusion When three CCSs are inserted in parallel to fix FNF, the OTC of three screws has obvious biomechanical advantages, especially in shear resistance and early postoperative weight‐bearing, which provides a mechanical basis for clinical selection of ideal spatial configuration for unstable FNF.